Proceedings of the 20th ACM International Conference on Information and Knowledge Management 2011
DOI: 10.1145/2063576.2063767
|View full text |Cite
|
Sign up to set email alerts
|

Finding dimensions for queries

Abstract: We address the problem of finding multiple groups of words or phrases that explain the underlying query facets, which we refer to as query dimensions. We assume that the important aspects of a query are usually presented and repeated in the query's top retrieved documents in the style of lists, and query dimensions can be mined out by aggregating these significant lists. Experimental results show that a large number of lists do exist in the top results, and query dimensions generated by grouping these lists ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 33 publications
0
41
0
Order By: Relevance
“…In addition, the performance of related faceted search methods and techniques in all phases is evaluated and described. Dou et al [4] developed QDMiner system to automatically extract facet hierarchies for keywords by aggregating frequent lists from free text, HTML tags, and reiterated regions within top search results. Anju G R and Karthik M [5] proposed a system implementing graphical model which is a supervised method.…”
Section: International Journal Of Computer Applications (0975 -8887)mentioning
confidence: 99%
“…In addition, the performance of related faceted search methods and techniques in all phases is evaluated and described. Dou et al [4] developed QDMiner system to automatically extract facet hierarchies for keywords by aggregating frequent lists from free text, HTML tags, and reiterated regions within top search results. Anju G R and Karthik M [5] proposed a system implementing graphical model which is a supervised method.…”
Section: International Journal Of Computer Applications (0975 -8887)mentioning
confidence: 99%
“…A valid query facet that describes Mars landing news could be {cnn, abc, fox }, which includes different news channels. In a recent work [7], Dou et al developed a system to extract query facets from web search results and showed the potential of doing so. However, the unsupervised method they proposed is far from optimal, and it does not improve by having human labels available.…”
Section: Query Subtopic/aspect Miningmentioning
confidence: 99%
“…Faceted search is similar to query facet extraction in that both of them use sets of coordinate terms to represent different facets of a query. However, most existing works for faceted search are build on as specific domain or predefined categories [7], while query facet extraction does not restrict queries in a specific domain, like products, people, etc.…”
Section: Faceted Searchmentioning
confidence: 99%
See 2 more Smart Citations